2012
DOI: 10.1371/journal.pone.0046763
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Quantitative Resistance-Specific Response upon Ralstonia solanacearum Infection in Tomato

Abstract: Bacterial wilt, caused by the soil-borne bacterium Ralstonia solanacearum, is a lethal disease of tomato, but the molecular mechanisms of the host resistance responses to R. solanacearum remain unclear. In this study, we report the first work describing the transcriptome of cultivar resistance and susceptible tomato cultivar after inoculation with R. solanacearum. To elucidate the characteristics of resistance early in the interaction, we analyzed microarrays for resistant cultivar LS-89 and susceptible cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 66 publications
4
96
0
Order By: Relevance
“…4C). Because R. solanacearum infections induce expression of tomato phenolic biosynthesis genes (Ishihara et al, 2012; Mitra, Milling, and Allen unpublished), we hypothesized that xylem sap from infected plants contains higher HCA concentrations that would benefit growth of the WT strain. However, we detected no differences in growth between WT and Δ fcs when they were grown in sap harvested from plants infected with WT or the Δ fcs mutant (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4C). Because R. solanacearum infections induce expression of tomato phenolic biosynthesis genes (Ishihara et al, 2012; Mitra, Milling, and Allen unpublished), we hypothesized that xylem sap from infected plants contains higher HCA concentrations that would benefit growth of the WT strain. However, we detected no differences in growth between WT and Δ fcs when they were grown in sap harvested from plants infected with WT or the Δ fcs mutant (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…LS-89, but not in susceptible tomato cv. Ponderosa (Ishihara et al, 2012). Histopathological studies of resistant and susceptible tomato found that R. solanacearum colonized fewer xylem vessels in wilt-resistant varieties (Grimault et al, 1994; Rahman et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major sources of bacterial wilt resistance in tomato originate from Solanum pimpinellifolium and S. lycopersicum var. cerasiforme (Ishihara et al ., ). ‘Hawaii 7996’ has been shown to have stable resistance against several R. solanacearum strains (Upreti and Thomas, ).…”
Section: Introductionmentioning
confidence: 97%
“…Although information on the mechanisms underlying defence responses against R. solanacearum is still limited, several reports have indicated that SA, JA and ET signalling are involved in resistance responses in tomato. A transcriptome analysis showed that expression of genes for JA/ET biosynthesis is increased in the resistant tomato cultivar LS‐89 in response to R. solanacearum infection (Ishihara et al ., ). Chen et al .…”
Section: Introductionmentioning
confidence: 97%